High Performance Speed of the Induction Motor Drives by the Predictive Control using Space Vector Modulation, ISSN 2230-9926 - Djeghdali Lakhdar; Naceri Farid; Sebti Belkacem (IJDR International Journal of Developpment Research, 2015)
This paper investigates the application of the generalized predictive control (GPC), in order to control the speed of the induction motor. This application is based on four main ideas :  reproducing decision basic mechanisms of human behaviour; the creation  of  an  anticipatory  effect  by  operation  of  the  path  to  follow  in  the  future;  defining  a  numerical  prediction  model; minimization of a quadratic criterion with finite horizon and the principle of receding horizon. The results proved that the induction motor with the MPC speed controller has superior transient response, and good robustness in face of uncertainties including load disturbance. Moreover, accurate tracking performance has been achieved.